Biosynthetic Mechanism of Lanosterol: Cyclization1. Issue 30 (9th June 2015) - Chen, Nanhao; Wang, Shenglong; Smentek, Lidia; Hess, B. Andes; Wu, Ruibo
Abstract The remarkable cyclization mechanism of the formation of the 6‐6‐6‐5 tetracyclic lanosterol (a key triterpenoid intermediate in the biosynthesis of cholesterol) from the acyclic 2, 3‐oxidosqualene catalyzed by oxidosqualene cyclase (OSC) has stimulated the interest of chemists and biologists for over a half century. Herein, the elaborate, state‐of‐the‐art two‐dimensional (2D) QM/MM MD simulations have clearly shown that the cyclization of the A–C rings involves a nearly concerted, but highly asynchronous cyclization, to yield a stable intermediate with "6‐6‐5" rings followed by the ring expansion of the C‐ring concomitant with the formation of the D‐ring to yield the "6‐6‐6‐5" protosterol cation. The calculated reaction barrier of the rate‐limiting step (≈22 kcal mol−1) is comparable to the experimental kinetic results. Furthermore all previous experimental mutagenic evidence is highly consistent with the identified reaction mechanism.